2021
DOI: 10.1002/jctb.6919
|View full text |Cite
|
Sign up to set email alerts
|

Surface and stability analysis of immobilized laccase on poly(ethylene terephthalate) grafted maleic anhydride nanofiber mat

Abstract: BACKGROUND: A poly(ethylene terephthalate) (PET) based carrier was used for enzyme immobilization due to its good physical and mechanical properties. However, its high hydrophobicity and chemically inactive properties hindered its capability as an enzyme carrier. This study developed a PET-based carrier by grafting PET with maleic anhydride (MAH) before electrospinning. This carrier was used to immobilize laccase and characterized based on its stability after immobilization.RESULTS: The highest laccase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…PPL was first immobilized on rPET/CA nanofibers using adsorption and then cross-linking methods with GA. In the literature, it has been reported that trypsin, laccase, and lipase were immobilized on PET-based nanofibers. ,,, However, none of these studies employed waste materials as the source of PET for their experiments. This study differs from its counterparts in the literature in that wastewater bottles are used as PET sources in the production of PET-based carrier nanofibers in PPL immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…PPL was first immobilized on rPET/CA nanofibers using adsorption and then cross-linking methods with GA. In the literature, it has been reported that trypsin, laccase, and lipase were immobilized on PET-based nanofibers. ,,, However, none of these studies employed waste materials as the source of PET for their experiments. This study differs from its counterparts in the literature in that wastewater bottles are used as PET sources in the production of PET-based carrier nanofibers in PPL immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…So, the two processes are difficult to be compatible in one pot . Moreover, the immobilization of enzyme on a solid carrier often results in a decrease of catalytic activity compared to the one of the free enzyme due to the increase of diffusion resistance of substrate on a solid carrier than that in bulk solution. , How to enhance the activity of immobilized enzymes, as well as the electron transfer efficiency between the enzyme and the electrode should also be taken into account.…”
Section: Introductionmentioning
confidence: 99%